Lifestyle Interventions for the Prevention of Type 2 Diabetes Mellitus - Schwarz, P.E.H.; Timpel, P. (Вестник Карагандинского университета, 2016)
Prevention of diabetes requires using of the achievements of basic science in clinical practice. For the last many years it was established that lifestyle factors in preventing type 2 diabetes in people at risk. Subsequent studies have provided important information on the actual implementation of diabetes prevention programs. In some countries efforts for diabetes prevention were realized but it is difficult to extrapolate on work according a large regional or national programs, specific items which must be scheduled for execution. For trained professionals in the field of health care, medical profile economists, health professionals and representatives of public organizations, capable of interacting with influential politicians. Political support is a very important component of this work. The article presents the results of a study that could help in the successful implementation of diabetes prevention programs in the «Practice of the real world.
Keywords: prevention of type 2 diabetes; diabetes mellitus; lifestyle interventions; health care